Gladys Black letter to Vernon M. Kleen regarding Snowy Owl counts, March 5, 1977 - Black, Gladyset al (1977)
Bird sightings and an enclosed map showing a count of Snowy Owls contributed by Gladys Black in a letter to Vernon M. Kleen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1976-1977. Epson - sheet feed/flatbed